PENGARUH PENGALAMAN, PENGETAHUAN, DAN AUDIT JUDGMENT TERHADAP OPINI AUDIT - Florentina '; Kirmizi '; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of experience, knowledge, and audit judgment on audit opinion. The population in this study is the auditor who working at the firm in the city of Pekanbaru, Medan, and Padang. Sampling technique used in this study is convenience sampling with total respondents 42 auditors. The type of data used is primary data by using questionnaires method. The data analysis technique used in this study is multiple regression analysis with the help of SPSS version 17. The result of this study showed that the experience has no significant effect on audit opinion. However, the knowledge and audit judgment has a significant effect on audit opinion. Simultaneously, all independent variables has significant effect on audit opinion. The value of adjusted R square is 20,7%, which mean that experience, knowledge, and audit judgment variable can explain 20,7% of audit opinion variable and the rest is explained by other variables that not included in this study.Keywords: experience, knowledge, audit judgment, and audit opinion.